Clinical and aesthetic outcome analysis of a case series of trigonocephaly patients after early fronto-orbital advancement. Issue 9 (September 2020) - Kampf, S.; Micko, A.; Schwartz, E.; Schopper, C.; Reinprecht, A.
Abstract: The timing of operation for trigonocephaly is recommended before the age of 1 year. To evaluate the outcome of a consecutive series operated in a single centre, the current study was performed. The study cohort comprised a retrospective single-centre series of 20 patients with trigonocephaly operated before the age of 12 months. Intra- and postoperative clinical data, as well as aesthetic outcome measured by two-dimensional asymmetry index (2D AI) and correction of the curvature on lateral and pictures from above were evaluated. Furthermore, to evaluate postoperative aesthetic outcome, a new classification (Grades I–IV) was proposed. The mean age of the cohort was 7.9 months. 2D AI changed from 0.049 pre- to 0.03 postoperatively ( P  = 0.165). The correction of the curvature in lateral pictures yielded a significant change on postoperative pictures ( P  = 0.002) as well as on pictures from above. Using the proposed classification, 16/20 (80%) patients had a postoperative outcome of Grade I, 4/20 (20%) Grade II. In patients operated before the age of 12 months an excellent (Grade I, AI <0.03) or good aesthetic (Grade II, adequate parents' or surgeon's opinion) result could be reached in all patients.